Evolutionary game analysis on supply side of the implement shore-to-ship electricity. (1st December 2021) - Chen, Jihong; Xiong, Wenjing; Xu, Lang; Di, Zhongjie
Abstract: The technology of shore-to-ship electricity (SSE) refers to the use of land power supply to power the ship during the berthing period, so that the ship stops using low sulfur fuel, which can help to promote the energy saving and emission reduction, as well as improve the comprehensive competitiveness of port. In this paper, we use the evolutionary game to analyze the interaction mechanism of tripartite behaviors, where the strategic space for government is non-incentive and incentive, port company is non-implement and implement, power company is non-investment and investment. From the case study, we observe that in the early stage of SSE construction, it's difficult for the port company and power company to solve the huge investment; thus, the government support, especially in the financial help, shows a huge impact to cover the SSE investment. In addition, the government considers gradually withdrawing from the market and no longer takes incentive measure; further, port company and power company should cooperate with each other, so that both carry out SSE transformation and unify standard to make the efficient SSE. Graphical abstract: Image 1